Ventricular noradrenaline concentrations in naïve and morphine-treated rats subjected to acute myocardial ischaemia. - Ko, W. W. (1988)
1 Ventricular noradrenaline concentrations in morphine-treated rats subjected to acute left coronary artery ligation were measured by high performance liquid chromatography with electrochemical detection. 2 In naïve rats, acute left coronary artery ligation induced a significant increase in right ventricular noradrenaline concentration at 5 min and significant decreases in left ventricular noradrenaline concentration at 3 and 10 min. 3 Acute morphine treatment did not significantly alter ventricular noradrenaline concentrations in rats subjected to acute coronary artery ligation. 4 Chronic morphine treatment caused significant declines in ventricular noradrenaline concentrations in rats subjected to acute coronary artery ligation. The reductions increased with duration of opiate treatment, and were reversed by opiate withdrawal. 5 These findings indicate that there is an increase in sympathetic activity during acute myocardial ischaemia. It is suggested that chronic morphine treatment may be able to retard this response, and consequently to lessen the occurrence of early ventricular arrhythmias resulting from acute myocardial ischaemia.